Answer:
4
Step-by-step explanation:
-2 + 6 = 4
Answer is in the file below
tinyurl.com/wpazsebu
Remember
x^-m=1/(x^m)
u^-3=1/(u^3)
1/(u^3)=1/125
therefor
u^3=125
u=5
x=-3
easy
y=-3-13
y=-16
correct
normally, y is output
(x,y)
chose al second numbers
0,3 are all acceptable
B and D
y=mx+b
m=-3
y=-3x+b
sub point
(x,y)
(1,-2)
-2=-3(1)+b
-2=-3+b
1=b
y=-3x+1
remember (x,y) you keep swtiching those
The standard form for the equation of a circle is :
<span><span><span> (x−h)^</span>2</span>+<span><span>(y−k)^</span>2</span>=<span>r2</span></span><span> ----------- EQ(1)
</span><span> where </span><span>handk</span><span> are the </span><span>x and y</span><span> coordinates of the center of the circle and </span>r<span> is the radius.
</span> The center of the circle is the midpoint of the diameter.
So the midpoint of the diameter with endpoints at (−10,1)and(−8,5) is :
((−10+(−8))/2,(1+5)/2)=(−9,3)
So the point (−9,3) is the center of the circle.
Now, use the distance formula to find the radius of the circle:
r^2=(−10−(−9))^2+(1−3)^2=1+4=5
⇒r=√5
Subtituting h=−9, k=3 and r=√5 into EQ(1) gives :
(x+9)^2+(y−3)^2=5